INCUSENSE: A BABY INCUBATOR WITH REAL TIME MONITORING & REGULATION OF VITALS - Natasha Mukhtiar; Saeed Ahmed; Beena Kumari; Daina Devi; Aisha Ahsan; Anum Fatima; Muhammad Fahad Shamim (Spectrum of Engineering Sciences, 2025)
Premature birth rate in Pakistan is alarming, with a study of data from obstetrics departments revealing that over 21% of more than 1,700 newborns were premature. A UNICEF survey on newborn health confirmed that preterm birth was the leading cause of infant mortality in 2015, accounting for over 39.3% of cases. Premature Babies, particularly those born before 37 weeks of gestation, often need oxygen therapy or supplemental oxygen due to their underdeveloped lungs' inability to perform necessary respiratory functions. Traditional neonatal incubators continue to have manual setting for the level of oxygen, which in practice results in some variation in patient care. Therefore, there is a need for intelligent incubators that can regulate oxygen saturation autonomously, to stabilize the results for hypoxic infants in particularly those, born between 34 and 37 weeks. This project will deliver a novel intelligent neonatal incubator, which provides a safe and stable controlled environment for preterm neonates by adjusting the temperature and humidity to the ideal ranges. It allows tracking and modifying oxygen concentration on a real time basis to improve the oxygenation and is helpful for less healthcare resource limited regions. It has sensors, an EPS32 based control system for real time monitoring and adjusting, so that it can provide a stable environment. Temperature is controlled by the heater fan system; humidity control is passive and the oxygen flow controlled using an actuator-driven servo motor attached to the flow meter. This developmental approach is expected to revolutionize the care of neonates. The system has been demonstrated to accurately control temperature (±0.3-0.5°C), humidity (±0.5-1%), and oxygen delivery (±0.2-1 L/min) according to a range of baseline oxygen saturation. With such precise experiments, these control trials represent a validation in the reliability and clinical potential of the system, validating the potential of advanced control systems in neonatal care and implying further research towards even better control for system effectiveness in addition to adaptation to develop a system that will effectively control the Temperature and Humidity using the baby incubators with a feature to regulate oxygen supply to Babies. In conclusion we found clinically significant value in this study, which can be used as an application of care of preterm babies in the NICU, by managing supply and delivery of oxygen.